2021
DOI: 10.1002/celc.202100281
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Electrodes: Atomic Palladium and Gold in Polyaniline

Abstract: Electrochemically deposited Pd m Au n metal clusters on a polyaniline-coated Pt electrode have been shown to exhibit an "ordering effect", in which the catalytic activity for n-propanol oxidation depends sensitively on the precise order that the metal atoms are deposited. For example, tri-atomic Pd 2 Au clusters exhibit different catalytic activity for electrodeposition order PdÀ PdÀ Au compared to PdÀ AuÀ Pd on the polyaniline (PANI)/Pt matrix. In this work, we utilize density functional theory (DFT) to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…It will be demonstrated that the PANI/AuCl 4 − complex is stable prior to the reduction process. However, in contrast to the work of Janata et al [ 11 , 12 , 15 ], we do not see any signs of atomic Au species after the controlled reduction of these PANI/AuCl 4 − complexes. Instead, we do clearly observe the formation of Au NPs.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It will be demonstrated that the PANI/AuCl 4 − complex is stable prior to the reduction process. However, in contrast to the work of Janata et al [ 11 , 12 , 15 ], we do not see any signs of atomic Au species after the controlled reduction of these PANI/AuCl 4 − complexes. Instead, we do clearly observe the formation of Au NPs.…”
Section: Introductioncontrasting
confidence: 99%
“…The latter even showed electrochemical activity towards the oxidation of alcohols with respect to their order of deposition [ 14 ]. Recently, these results were backed up by density functional theory calculations [ 15 ]. It was shown that such triatomic clusters of Au and Pd are indeed stabilized on the quinone ring by a large interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…While the calculated curve also indicates a linear increase, there is a concentration difference of around 9×10 [17][18][19][20]. A different view is advocated by Janata and co-workers in their work on atomic metals [7,8,11,21,22]. Here, AuCl 4 − is reduced at its initial imine site resulting in a single Au atom which becomes stabilized in the PANI framework.…”
Section: Discussionmentioning
confidence: 99%
“…The latter even showed electrochemical activity towards the oxidation of alcohols with respect to their order of deposition [10]. Recently, these results were backed up by density functional theory calculations [11]. It was shown that such triatomic clusters of Au and Pd are indeed stabilized on the quinone ring by a large interaction energy.…”
Section: Introductionmentioning
confidence: 93%
“…Besides Au, also Cl, F, O and N have been detected with the following average quantities across all measured samples: Cl=(1.12±0.49)×10 17 atoms/cm 2 , F=(4.22±3.76)×10 15 atoms/cm 2 , O= (3.06±0.53)×10 17 atoms/cm 2 , and N=(4.29±0.37)×10 17 atoms/cm 2 . The residual amounts of F must stem from the PANI deposition process which is carried out in HBF 4 .…”
Section: Quanti Cation Of the Introduced Aumentioning
confidence: 95%